Immunomodulatory properties of bacteriocin UL4 from lactobacillus plantarum contribute to reduced incidence of colon cancer in rats - Saiful Yazan, Latifah; M. Z., Noraina; Foo, H. L.; Mohammed Alitheen, Noorjahan Banu; M., Hair-Bejo; M., Saidi (2009)
Probiotics are known to modulate immunity in animals and human subjects, and to inhibit colon carcinogenesis in experimental models. Nevertheless, the effects of metabolites from the probiotics are not well understood. In this study, the effects of bacteriocin UL4 (UL4), a metabolite from probiotic Lactobacillus plantarum on the immune system were investigated in the azoxymethane (AOM)-induced colon cancer rats. Briefly, 60 male Sprague Dawley rats 6 weeks of age with average body weight of 90-100 g were induced with azoxymethane (AOM) (15 mg/kg body) subcutaneously, once a week for two weeks. Following that, the rats were randomly divided into 5 groups (15 rats per group) ,which were (1) positive control (induced with colon cancer, unfed with UL4); (2) fed with 0.25% of UL4; (3) fed with 0.5% of UL4; (4) fed with 0.75% of UL4 and (5) negative control (not induced with colon cancer, unfed with UL4). After 6 months induction of colon cancer, rats were treated with different percentages of UL4 for 12 weeks. After 36 weeks, all rats were killed and blood was withdrawn. The immune cell suspensions were prepared from spleen and thymus of the rats. All groups treated with UL4 showed significant increased level of tumor necrosis factor alpha (TNFα) and interferon gamma (IFNγ) in the serum, spleen and thymus cell suspensions for 24, 48 and 72 hours of incubation time compared to the positive control group (p<0.05). In conclusion, UL4 stimulates the secretion of TNFα and IFNγ, leading to the activation of specific immune responses contributing to its role in inhibition of tumorigenesis (reduced crypt multiplicity and number of ACF in the rats induced with colon cancer).